Tekstur Yoghurt Susu Kambing dengan Perbedaan Jenis Starter dan Lama Fermentasi - Sujono Sujono; Mochamad Rizal Ali Rofat; Hendra Kusuma; Khusnul Khotimah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
One of the products of the Campus Intellectual Product Business Development Program (PPUPIK) is goat milk yoghurt, yoghurt itself is a drink made from fermented milk by lactic acid bacteria which is controlled. Yoghurt texture determines the tastes of consumers. Therefore it is necessary to study the texture of yoghurt with different types of starters and length of fermentation. This is to obtain yoghurt with maximum nutritional quality and a soft, thick texture to meet consumer tastes. The process of making yoghurt with fermentation time (6, 12, 18 and 24) hours with 37°C temperature and the type of starter bacteria (Streptococcus thermophillus, Lactobacillus bulgaricus and combinations), so that there were 12 treatments and repeated three times. The parameters observed by panellists are texture. The texture analysis of yoghurt was analyzed by de Garmo to find out the most appropriate treatment and much interest among panellists. Panellists favoured the de Garmo test results for 24-hour fermentation using the Lactobacillus bulgaricus bacteria with the highest texture product value of 2.10 (regular thick yoghurt).